Evaluación de las aulas virtuales de la carrera de Pedagogía de las Ciencias Experimentales: Informática - Chicaiza Chicazia, Bryan Stalin (2024)
The advent of ICT in education has transformed teaching processes. The integration of Virtual Classrooms, in particular, has contributed to interactive learning and the development of communication skills. This research aims to evaluate the virtual classrooms of the Pedagogy of Experimental Sciences: Informatics program at UNACH. To achieve this goal, a quantitative approach was adopted, employing a non-experimental cross-sectional design with a descriptive scope. Data was collected using a 24-item questionnaire administered to a sample of 202 students. The research findings reveal that more than 70% of the responses in all five dimensions analyzed fell within the "Agree" or "Strongly Agree" categories. In this regard, students perceive that the content, interaction, assessment, and activities integrated into the virtual environment, contribute to more dynamic and flexible learning. However, a smaller percentage—less than 20%—fell within the "Disagree" or "Strongly Disagree" categories. These results highlight areas for improvement in future teacher training processes to better leverage the resources offered by virtual platforms. Overall, according to students' perceptions, the virtual classrooms of the Pedagogy of Experimental Sciences: Informatics program, serve as a valuable supplement to face-to-face education, enhancing communication, interaction, and motivation to learn.